1998
DOI: 10.1063/1.367811
|View full text |Cite
|
Sign up to set email alerts
|

New bulk amorphous Fe–(Co,Ni)–M–B (M=Zr,Hf,Nb,Ta,Mo,W) alloys with good soft magnetic properties

Abstract: We have found that an amorphous phase with a wide supercooled liquid region reaching 85 K before crystallization is formed in Fe–(Co, Ni)–(Zr, Nb, Ta)–B, Fe–Co–(Zr, Nb)–(Mo, W)–B and Co–Fe–Zr–B systems. The high stability of the supercooled liquid enabled the production of bulk amorphous alloys with diameters up to 5 mm by copper mold casting. These amorphous Fe–(Co, Ni)–M–B alloys exhibit good soft magnetic properties, i.e., saturation magnetization of 0.95 to 1.1 T, low coercivity of 1 to 8 A/m, Curie temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(61 citation statements)
references
References 16 publications
2
54
0
5
Order By: Relevance
“…For our investigations, we have chosen amorphous Co 56-Fe 16 Zr 8 B 20 alloy which is known to exhibit large super-cooled liquid region and excellent soft magnetic properties, e.g. high permeability in the frequency range up to 1 MHz [3]. In a previous work [4] we have shown that short-time BM of this alloy results in mechanically-induced crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…For our investigations, we have chosen amorphous Co 56-Fe 16 Zr 8 B 20 alloy which is known to exhibit large super-cooled liquid region and excellent soft magnetic properties, e.g. high permeability in the frequency range up to 1 MHz [3]. In a previous work [4] we have shown that short-time BM of this alloy results in mechanically-induced crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…The recent research on soft-magnetic nanocomposites was reviewed by several authors [4][5][6][7][8]. The search for bulk amorphous metallic glasses with good soft magnetic properties [8], further led to the discovery of Co-rich bulk amorphous alloys in the Co-Fe-M-B alloy system (M: Zr, Nb) [9]. The new Co-based amorphous alloys exhibit low coercivity and stable high permeability in the frequency range up to 1 MHz.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The materials are usually fabricated either by rapid quenching from the molten state or in thin film form by sputtering. They can exhibit unique mechanical properties, 3 improved corrosion resistance, 4,5 very soft magnetic response, 6 and high magnetic moment and Curie temperatures. From a technological point of view, they are the best-known materials for stress sensing, having magnetomechanical coupling factors k 2 ͑ratio of energy transfer between the mechanical and magnetic subsystems͒ approaching unity.…”
Section: Introductionmentioning
confidence: 99%